2018
DOI: 10.1002/ajmg.a.38705
|View full text |Cite
|
Sign up to set email alerts
|

Functional independence of Taiwanese children with Prader–Willi syndrome

Abstract: Prader-Willi syndrome (PWS) is a genetic disorder with obesity, developmental delay, short stature, and behavioral abnormalities. The study aimed to assess the functional independence in children with PWS. The Functional Independence Measure for Children (WeeFIM) was used to evaluate 81 children with PWS (44 boys and 37 girls) with a median age of 11 years 1 month (range 2 years 8 months to 20 years 2 months) were recruited between January 2013 and December 2016. The mean total WeeFIM score was 103.8 (maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Among those tools, PEDI (Pediatric Evaluation of Disability Inventory) and WeeFIM are most frequently used and both had been validated in Chinese children with disabilities [ 14 , 46 ]. The PEDI instrument, composed of 197 questions, is more time-consuming and costly in the setting of an outpatient department in Taiwan, while the WeeFIM instrument is more convenient and showed reliability in our previous studies regarding functional independence in Taiwanese children with rare diseases [ 18 , 19 ].The WeeFIM is a reliable instrument to evaluate the functional status of children with disabilities. It was first validated in American children [ 47 ], and then used by Wong et al [ 14 ] and others [ 13 ] in similar studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those tools, PEDI (Pediatric Evaluation of Disability Inventory) and WeeFIM are most frequently used and both had been validated in Chinese children with disabilities [ 14 , 46 ]. The PEDI instrument, composed of 197 questions, is more time-consuming and costly in the setting of an outpatient department in Taiwan, while the WeeFIM instrument is more convenient and showed reliability in our previous studies regarding functional independence in Taiwanese children with rare diseases [ 18 , 19 ].The WeeFIM is a reliable instrument to evaluate the functional status of children with disabilities. It was first validated in American children [ 47 ], and then used by Wong et al [ 14 ] and others [ 13 ] in similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…The WeeFIM questionnaire was designed for primary caregivers to record their child’s abilities directly, and in 2002, Wong et al translated the questionnaire into Chinese. It has been used to estimate functional independence in children from 6 months to 7 years of age, and up to 21 years of age in those with developmental disabilities [ 17 , 18 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…28 In general, through an interdisciplinary inpatient rehabilitation approach, children made significant changes from admission to discharge, which is supported by the previous studies that reported an overall change in outcomes after rehabilitation. 2,5,14,17,18,[29][30][31] Functional gains, as measured by the Wee-FIM instrument, vary depending on diagnoses, time from injury/diagnosis to rehabilitation admission, age, and LOS. The results of this study showed significant differences in gains across age and impairment groups, children older than 7 years made larger gains than younger children.…”
Section: Discussionmentioning
confidence: 99%